Exploring the roles of narcissism, uses of, and gratifications from microblogs on affinity‐seeking and social capital. Issue 2 (11th September 2014) - Mo, Ruo; Leung, Louis
<x xml:space="preserve">Abstract</x> The purpose of this study is to examine how the uses and gratifications of microblogs (i.e. Sina Weibo) can influence interpersonal relationships, especially in affinity‐seeking and perceived social capital. Data were gathered through an online questionnaire with a sample of 431 Weibo users surveyed throughout mainland China. Results show that (i) narcissism, content‐, and social‐gratification were positively related to intensity of Weibo use, (ii) intensity of Weibo use and process‐gratification were positively related to strategic performance, whereas only content‐gratification positively predicted affinity competence. (iii) content‐ and social‐gratification positively predicted bridging social capital, whereas convenience‐gratification and affinity‐seeking predicted bonding social capital, and (iv) intensity of Weibo use was positively related to both types of social capital only when Weibo gratifications were not included in the regression equations. Implications and suggestions for future research are discussed.